Pemetaan Risiko Kebkaran Di Kampus I Universitas Muhammadiyah Surakarta - Fatra, Imam Sufriandi, Dwi Astuti, SKM., M.Kes, Miftahul Arozaq, S.Si (2015)
Fires can occur at any time and lead to financial losses and damages to people. Fires in campus I Muhammadiyah University of Surakarta ( UMS ) have also occurred in laboratory space that destroyed the laboratory equipment such as desks, oven, stove, Air Conditioner ( AC ), a projector and a fan. This study aims to provide information about fire risk in Campus I Universitas Muhammadiyah Surakarta area through mapping and seeing safety level of the buildings in the area. This is a descriptive study with observational methods. The observed objects of this study are all of the rooms and buildings located in Campus I Universitas Muhammadiyah Surakarta area. The fire risk assessment uses Risk Matrix-Fire Risk, which afterwards is mapped using ArcGIS application. The result in Universitas Muhammadiyah Surakarta shows 203 rooms (86,74%) low fire risk, 16 rooms (6,84%) moderate fire risk, 13 rooms (5,55%) high fire risk, and 2 rooms (0,85%) extreme fire risk. The building safety is examined through observing all of the buildings in Campus I Universitas Muhammadiyah Surakarta using checklist sheets. The result of these checklist sheets presents that there are still plenty of unfulfilled regulations, such as regulations of a general state of a building, regulations of an emergency exit along with its access, regulations of fire protection system, and regulations of First Aid.